Seasonal dynamics of microbial communities link to summer-autumn aquaculture disease outbreaks in Sanggou Bay - Lu, Longfei; Ni, Lingfang; Ai, Chunxiang; Zhang, Dongdong; Zheng, Pengfei; Li, Xuejing; Liu, Xin; Dang, Hongyue (Frontiers in Marine Science, 2025)
Marine microorganisms play a vital role in aquaculture by influencing water quality and the health of cultured species. Relative to conventional mono-species aquaculture, integrated multi-trophic aquaculture is more environmentally friendly and economically sustainable. However, the temporospatial dynamics of the microbial community in different aquaculture modes and their roles in the seasonal diseases of aquacultural organisms are largely unknown. Here, the seawater bacterial communities and potential pathogens were investigated over thirteen months in three different aquaculture types in Sanggou Bay, a typical maricultural area with nearly 60 years of history. Seasonality played a primary role, while aquaculture type played a subtle role in shaping the bacterioplankton community. Diverse potential pathogens were identified, and r-strategist bacteria, most of which were opportunistic pathogens and typified by Vibrio species, increased and dominated in late summer and autumn, a period of high-risk disease outbreaks in mariculture organisms. Network analyses indicated that the increase in r-strategist bacteria reduced the complexity of microbial interactions, and Vibrio halioticoli (OTU1389), a hub species with extensive positive correlations to other Vibrio OTUs, likely contributed to the increase of pathogenic vibrios due to its macroalgae degradation capability. The major potential pathogenic Vibrio OTUs were further corroborated by genome analyses and environmental simulation experiments using pathogenic Vibrio isolates, including two new species. Moreover, we found seawater dissolved oxygen, temperature, and transparency correlated significantly with the bacterioplankton temporospatial dynamics and the seasonal outbreaks of bacterial pathogens. Our results emphasize the necessity of synchronically monitoring the bacterial community, its pathogens-stimulating species, such as V. halioticoli and other macroalgae-degrading bacteria, and critical physicochemical parameters for predicting and preventing pathogen outbreaks in mariculture.